Analisis Strategi Dakwah Guru Ngaji dalam Menanamkan Nilai-Nilai Akhlak di Desa Pidung Kecamatan Keliling Danau - Ronaldo, Ronaldo; Zuhdi, Ahmad; H Nanda, Dendy (Journal of Da'wah, 2022)
This research is inspired by the phenomenon of some teenagers who do not joined in the recitation is takes place in the mosque, then the lack of interest in the youth who do not joined in the recitation is caused by some teenagers are lazy with younger children, some of them feel that they have been able to attend the recitation, many of students school task that must be completed quickly. This study used qualitative research methods. The key informants in this study were the qur’an teacher and the children in Pidung Village. The validity of data used triangulation techniques to test the validity of data related to the research problem being studied by researcher. Then, to analyse the data, the resercher was used data reduction, Data display and verification and conclusion drawing. The results of study showed that the strategy da’wah of Qur’an Teacher to the teenagers  at Pidung Village were as follows: 1) Sentimental strategy, this strategy focuses on aspects of the heart and moves feelings by giving good advice with gentleness. This strategy is usually used by Qur’an teacher in giving the tausiah. 2) Rational strategy, this strategy focuses on aspects of the mind to encourage the Qur’an teacher students thought rationlaly, anticipate and take lessons. This strategy is used by discussing or telling the stories. 3) Sensory strategy, which is this strategy focuses on to aspects of five senses and follows to the results of research and experiments. This strategy is used by religious practice and exemplary.